Privacy of Internet Users in the Era of Transformative Marketing - Muhammad Farooq; Qasim Ali Qureshi (Journal of Management Practices, Humanities and Social Sciences, 2020)
This research aims to investigate the customer concern of privacy over the internet pertaining to e-commerce companies in the era of transformative marketing. The paper discusses different drivers and challenges of customer's data protection. The article also explores the two prominent prospects on internet privacy; the